Essays in financial econometrics - Franco, João Pedro Malim (2025)
This thesis presents four essays in financial econometrics, with a focus on systemic and tail risk modeling, volatility transmission, and portfolio optimization - particularly within cryptocurrency and emerging markets. The first two essays explore systemic risk estimation and joint tail risk modeling using CoVaR in high-frequency framework and optimal transport methods. The third essay integrates Choquet portfolio theory with interpretable machine learning techniques. The fourth analyzes volatility networks in the Brazilian equity market via stochastic volatility models and factor-adjusted VARs. Together, these studies offer methodological advances and practical insights for risk assessment in modern financial systems.